Entrepreneurship Through Start-ups in Hill Areas Using Photovoltaic Systems - Chandani Sharma; Anamika Jain (Bulletin of Electrical Engineering and Informatics, 2017)
There is large potential for generating solar power in Uttarakhand (India) endowed with natural resources. The extensive use of solar energy through solar PV panels in Distributed and Renewable Electricity Generation is significant to utilize multi climatic zones of hilly areas. In this regard, UREDA (Uttarakhand Renewable Energy Development Agency) targets to achieve a huge boost of solar PV battery backup with approved subsidy budget of INR 6 billion to 50 billion by 2019/20 under JNNSM (Jawaharlal Nehru National Solar Mission). This investment will increase productivity, enhance employment opportunities and improve quality of education. However, maximization of power output from panels used for same is achieved through use of MPPT (Maximum Power Point Trackers). The commercially installed solar power systems can be made to accomplish higher efficiency by implementing MPPT systems in start ups. In this paper, the effort is made to use MPPT system designed by intelligent controller for implementation in PV based utility systems. The regulated voltage output from MPPT system is obtained irrespective of fluctuations in environment. These variations are tested for changing temperature and irradiance due to shading or partial unavailability of sun. The results of same have been optimized through MATLAB/SIMULINK. The model designed is intended to be a beneficial source for PV engineers and researchers to provide high efficiency with the use of MPPT.